Prognostic effects of cytokine levels on patients treated with taxane and zoledronic acid for metastatic breast cancer in bone (BEAT-ZO) (KCSG BR 10-13). (June 2021) - Kim, Ju Won; Lee, Soohyeon; Kim, Hye Sook; Choi, Yoon Ji; Yoo, Jinho; Park, Keon Uk; Kang, Seok Yun; Park, Yeon Hee; Jung, Kyung Hae; Ahn, Jin-Hee; Oh, Ho-suk; Choi, In Sil; et al.
Abstract: Advanced breast cancer frequently metastasizes to the skeleton causing major mobility issues and hazards to quality of life. To manage osteolytic bone metastasis, bone-modifying agents and chemotherapy are recommended as the standard of care. Here, we investigated serologic biomarkers that might be associated with prognosis in breast cancer patients treated with zoledronic acid (ZA) and taxane-based chemotherapy. We collected serum samples from breast cancer patients with bone metastasis who received taxane plus ZA as palliative treatment. Fourteen biomarkers of angiogenesis, immunogenicity, and apoptosis were assessed, and the correlation between serum cytokine levels and patient's prognosis was statistically analyzed. Sixty-six patients were enrolled, and samples from 40 patients were analyzed after laboratory quality control. Patients with low baseline PDGF-AA, high IFN-γ, low MCP-2, low TGF-β1, and low TNF-α were significantly associated with longer progression-free survival (PFS). Decreasing VEGF and TNF-α and increasing FGF-2 and PDGF-AA in the early treatment phase indicated longer PFS. In univariate and multivariate analyses, low TGF-β1 and TNF-α and high IFN-γ at baseline were associated with a significantly low hazard ratio for disease progression. Further, we designed a risk score with TGF-β1, TNF-α, and IFN-γ levels, which could prognosticate patients for PFS. In conclusion, serum cytokine level, such as TGF-β1, TNF-α, and IFN-γ, could be a potential prognostic biomarker for breast cancer patients with bone metastasis treated with ZA and taxane-based chemotherapy.